Settler Colonial Governance in Nineteenth-Century Victoria - Boucher, Leigh (ANU Press, 2015)
This collection represents a serious re-examination of existing work on the Aboriginal history of nineteenth-century Victoria, deploying the insights of postcolonial thought to wrench open the inner workings of territorial expropriation and its historically tenacious variability. Colonial historians have frequently asserted that the management and control of Aboriginal people in colonial Victoria was historically exceptional; by the end of the century, colonies across mainland Australia looked to Victoria as a 'model' for how to manage the problem of Aboriginal survival. This collection carefully traces the emergence and enactment of this 'model' in the years after colonial separation, the idiosyncrasies of its application and the impact it had on Aboriginal lives.